Flouting Maxims in Jackson Wang’s Interview on the DIVE Studios Podcast - Nouva El Aziza Ardyningrum (Jurnal Ilmiah Telaah, 2026)
This study aims to identify the types of flouting maxims and the reasons behind their use in Jackson Wang’s interview on the DIVE Studios podcast. This research employed a qualitative approach. The data consisted of utterances produced by Jackson Wang that contained flouting maxims. The study applies Grice’s (1975) Cooperative Principle to identify the types of flouting maxims. The findings revealed 38 utterances containing flouting maxims, consisting of 18 instances of flouting maxim of quantity, 13 of flouting maxim of relation, 4 of flouting maxim of quality, and 3 of flouting maxim of manner. The findings also indicate that the speakers flouted conversational maxims for various communicative purposes, including avoiding direct answers, emphasizing ideas, expressing emotions, maintaining privacy, creating humor, and fostering a more natural interaction.